Drug-Eluting Beads Bronchial Arterial Chemoembolization Combined with Immunotherapy Resulted in Pathological Complete Response of Squamous Cell Lung Cancer: A Case Report - He G; Yang K; Gao Z; Zhang X; Han A (International Medical Case Reports Journal, 2024)
Guanghui He,1 Kunning Yang,2 Zhi Gao,1 Xiaofa Zhang,3 Aiqiang Han4 1Interventional Department, Weifang No. 2 People’s Hospital, Weifang, People’s Republic of China; 2Respiratory Medicine Department, Weifang No. 2 People’s Hospital, Weifang, People’s Republic of China; 3Interventional Department, Anqiu People’s Hospital of Weifang, Weifang, People’s Republic of China; 4Department of Gerontology, Weifang No. 2 People’s Hospital, Weifang, People’s Republic of ChinaCorrespondence: Aiqiang Han, Department of Gerontology, Weifang No. 2 People’s Hospital, Weifang, Shandong Province, People’s Republic of China, Email aiqianghan@139.comAbstract: The incidence of lung cancer is the highest among all tumors, and treatment has become an urgent problem to be solved. The Drug-eluting bead-based bronchial arterial chemoembolization (DEB-BACE) combination immunotherapy is a rare neoadjuvant therapy for lung cancer surgery, which can significantly reduce the time it takes for lung cancer patients to undergo surgery.We report a male patient, aged 59-year-old, with Stage-III b squamous cell lung cancer accompanied by hemoptysis underwent surgical resection after DEB-BACE combination immunotherapy treatment 21 days later without obvious adverse events. A pathologic complete response (pCR) was observed postoperatively, and the patient has made a successful recovery. The DEB-BACE combined with immunotherapy might be a new neoadjuvant therapy option for locally advanced non-small cell lung.Keywords: drug-eluting bead-based bronchial arterial chemoembolization, immunotherapy, squamous cell lung cancer, case report